2007
DOI: 10.1097/gim.0b013e31803068b1
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase G-463A polymorphism and lung cancer: A HuGE Genetic Susceptibility to Environmental Carcinogens pooled analysis

Abstract: Myeloperoxidase is a phase I metabolic enzyme that converts the metabolites of benzo [a]pyrene from tobacco smoke into highly reactive epoxides. A polymorphism in the promoter region of myeloperoxidase (463G¡A) has been found to be inversely associated with lung cancer; differences in the association with age and gender have been suggested. We conducted a pooled analysis of individual data from 10 studies (3688 cases and 3874 controls) from the Genetic Susceptibility to Environmental Carcinogens database. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…The possible mechanism by which rs2333227 may affect lung cancer risk is to decrease MPO gene expression by destroying a transcript-binding site. Rs2333227 has been investigated extensively for the association with lung cancer risk, and a recent pooled-analysis indicated that the association did exist, although with weak significance [11,[27][28][29][30][31][32][33] . Hence, we did not choose this SNP for the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible mechanism by which rs2333227 may affect lung cancer risk is to decrease MPO gene expression by destroying a transcript-binding site. Rs2333227 has been investigated extensively for the association with lung cancer risk, and a recent pooled-analysis indicated that the association did exist, although with weak significance [11,[27][28][29][30][31][32][33] . Hence, we did not choose this SNP for the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent research has shown that MPO may play a major role during pulmonary carcinogenesis, such as the inhibition of nucleotide excision repair in human pulmonary epithelial cells [8] , DNA damage caused by hypochlorous acid and other reactive oxygen species [9] and the methylation of P16 [10] . Clinical and epidemiological studies on the association between the MPO G463A polymorphism and lung cancer sus-www.chinaphar.com Gu JD et al Acta Pharmacologica Sinica npg ceptibility indicate that the association exists in Caucasian and Chinese populations, although it is not significant [11] . Because both experimental and epidemiological studies indicated that MPO could play an important role in pulmonary carcinogenesis, the hypothesis that polymorphism(s) of MPO may affect lung cancer risk deserved further study, both independently and at the genome-wide level.…”
Section: Introductionmentioning
confidence: 99%
“…Conceivably, inadequate SCN Ϫ levels would aggravate MPO-produced injuries in patients suffering from inflammatory diseases including asthma. MPO activity has been linked to lung cancers among smokers (49) and also implicated in the pathogenesis of many neurodegenerative diseases (50-52). We find that MPO-caused injuries to a neuronal cell line (Neuro-2A) can be greatly reduced by SCN Ϫ (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, immunochemical studies revealed that MPO is expressed in microglia, astrocytes, and certain types of neurons, suggesting that MPO could play an important role in neurodegenerative disease ( 17 ), such as multiple sclerosis (18)(19)(20), Alzheimer's ( 21,22 ), and Parkinson's disease ( 23 ). Interestingly, MPO has even been implicated as a risk factor for some forms of cancers ( 24,25 ). Some of the earliest evidence that MPO plays a role in cardiovascular disease comes from studies showing that chlorotyrosine on LDL is increased in human vascular lesions ( 26 ).…”
Section: Mpo-mediated Ldl Malondialdehyde Formationmentioning
confidence: 99%